The “Safdarjung Method” of Estimation of Total Body Surface Area (TBSA) Burns in Major Amputees - Neha Chauhan; Karoon Agrawal; Shalabh Kumar (Indian Journal of Plastic Surgery)
Accurate estimation of total body surface area (TBSA) burns is the cornerstone of initiating correct fluid therapy in burns. The current formulae are designed for patients with intact body. However, the authors having worked at a high-volume burns center (Safdarjung Hospital, New Delhi, India) have encountered patients with major amputations presenting with burns. The existing formulae are inaccurate for estimating TBSA in major amputees, leading to inaccurate fluid estimation in such cases. The authors have designed a novel method to estimate TBSA burns in patients with major amputations that involves a “correction factor” to account for the amputated parts.